2011
DOI: 10.1111/j.1365-2427.2011.02685.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical time lags may delay responses of streams to ecological restoration

Abstract: Summary 1. Mounting interest in ecological restoration of streams and rivers, including that motivated by the Water Framework Directive, has stimulated examination of whether management and restoration measures in streams and their catchments have yielded measurable improvements in ecological status (‘health’). Evidence for the efficacy of diffuse‐source pollution reduction (including best management practices on land) has proven elusive. 2. Several hydrological and biogeochemical processes delay the responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(189 citation statements)
references
References 125 publications
3
183
0
Order By: Relevance
“…Comparable results were observed in the Mississippi River watershed, where currentyear NANI was estimated to influence riverine nitrate fluxes for 2-9 years (McIsaac et al 2001). The lag time of N leaching to rivers is dependent on hydrological and biogeochemical processes in the watershed (Hamilton 2012). Stable isotopic tracers (mainly 3 H) have shown that delivery times for surface runoff, soil water/shallow groundwater, and groundwater to river systems are on the order of months, years, and decades, respectively (Iqbal 2002;Phillips and Lindsey 2003;Sanford and Pope 2013;Tesoriero et al 2013).…”
Section: Cause Of the Lag Effect On Riverine N Exportmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable results were observed in the Mississippi River watershed, where currentyear NANI was estimated to influence riverine nitrate fluxes for 2-9 years (McIsaac et al 2001). The lag time of N leaching to rivers is dependent on hydrological and biogeochemical processes in the watershed (Hamilton 2012). Stable isotopic tracers (mainly 3 H) have shown that delivery times for surface runoff, soil water/shallow groundwater, and groundwater to river systems are on the order of months, years, and decades, respectively (Iqbal 2002;Phillips and Lindsey 2003;Sanford and Pope 2013;Tesoriero et al 2013).…”
Section: Cause Of the Lag Effect On Riverine N Exportmentioning
confidence: 99%
“…However, the calibration procedures for these models contain considerable uncertainty since measured riverine N fluxes are a mixture of N and water sources with different ages and the lag time is often larger than the temporal extent of available calibration data (Meals et al 2010;Bouraoui and Grizzetti 2014). Due to the complexities of understanding transit time and biogeochemical mechanisms for N passing through the soil profile, vadose zone, and groundwater to the river network (Meals et al 2010;Hamilton 2012;Sebilo et al 2013), the N leaching lag effect is not well addressed and formulated in most current watershed mechanistic models (Meals et al 2010;Sanford and Pope 2013;Bouraoui and Grizzetti 2014). For example, values for groundwater residence time in the SWAT model range from 0 to 500 days, which is much lower than estimated residence times (years to decades) derived from stable isotope tracers (mainly 18 O and 3 H) (Iqbal 2002;Phillips and Lindsey 2003;Tesoriero et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the relationships between nutrient use, nutrient delivery, biological response and ecosystem resilience in space and time are highly complex making it difficult to accurately predict recovery trajectories based on nutrient load reduction [22,23]. For example, any remediation may well take long periods of time due to within catchment storage and fractal functioning, while complex feed-back mechanisms and the confounding effects of climate change make it difficult to predict the direction of biological improvement [24][25][26][27]. The need for a more holistic approach to improving water quality including biophysical restoration (e.g., riparian management, flow regulation and food web enhancement [28,29]) is increasingly being recognized, but there is no general recipe for success.…”
Section: Introductionmentioning
confidence: 99%
“…Biogeochemical cycling within freshwater lentic systems, including lakes, reservoirs, and ponds systems, can modify and/or delay N export via surface waters (Hamilton 2012). Naturally occurring lakes are a significant N sink (Seitzinger et al 2002, Mulholland et al 2008, Goodman et al 2011.…”
Section: N Transport Through and Transformation Within Lentic Systemsmentioning
confidence: 99%
“…In areas that have been used for agriculture for many years, groundwater can be contaminated with N and account for a significant portion of N flux into streams (Canter 1996, Howden et al 2011, Ator and Denver 2015. Because of the long residence time of groundwater, N from decades ago advects into streams today (Hamilton 2012) and will continue to do so for a long time, even if N application immediately ceased. This lag-time between agricultural management practices and changes in stream water quality presents a problem for quantifying the impacts of alternative agriculture (which is likely to be a relatively new practice) on N fluxes in surface waters.…”
Section: Introductionmentioning
confidence: 99%